Analiza požara pri prometni nezgodi - Vidmar, Peter (Strojniški vestnik, 2003)
This paper is an attempt to define fire behaviour. The work is based on an analytical study of a fire's origin, its development and spread. The study is based on thermodynamics, heat transfer and a study of hydrodynamics and combustion, which represent the basis of fire dynamics. The article described a practical example of a leak of hazardous chemicals from a tank truck. Because of a flammability of the fluid, a fire may start. We have tried to model the fire propagation around a flammable-gas warehouse and show how the surrounding area could be affected. The model also considers weather conditions in particular the wind speed and direction. The computer code SaferTrace, which is based on zone models was used to do this. This means, that the phenomena are described with simplified physical and empirical equations, and one of the disadvantages of this computer code is its inability to consider the ground topology. Mathematical models are presented and they show the propagation of a hazardous fluid in the environment, while considering the metereological data.
Keywords: nezgode prometne; analize požarov; modeli matematični; oblaki plinski; prometne nesreče; razlitje; požari; matematični modeli